2019
DOI: 10.1002/hep.30150
|View full text |Cite|
|
Sign up to set email alerts
|

Ductular Reaction in Liver Diseases

Abstract: Ductular reaction (DR) is characterized by the proliferation of reactive bile ducts induced by liver injuries. DR is pathologically recognized as bile duct hyperplasia and is commonly observed in biliary disorders. It can also be identified in various liver disorders including non-alcoholic fatty liver disease. DR is associated with liver fibrosis and damage, and the extent of DR parallels to patient mortality. DR raises scientific interests because it is associated with transdifferentiation of liver cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
339
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 299 publications
(352 citation statements)
references
References 72 publications
(133 reference statements)
11
339
0
2
Order By: Relevance
“…The origin of these cholangiocyte‐like cells is still debated and likely depends on the nature of the liver injury. Indeed, in different pathologic settings, they have been shown to originate from reactive cholangiocytes, hepatic and biliary progenitor/stem cells (HPCs), or transdifferentiated hepatocytes/hybrid hepatocytes (sex‐determining region Y‐box 9–positive [Sox9 + ] hepatocyte nuclear factor 4 alpha–positive) . This heterogeneity has rendered the identification of common, specific markers of DRCs quite challenging as different DRCs can express different markers depending on their origin and the nature of the injury .…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
“…The origin of these cholangiocyte‐like cells is still debated and likely depends on the nature of the liver injury. Indeed, in different pathologic settings, they have been shown to originate from reactive cholangiocytes, hepatic and biliary progenitor/stem cells (HPCs), or transdifferentiated hepatocytes/hybrid hepatocytes (sex‐determining region Y‐box 9–positive [Sox9 + ] hepatocyte nuclear factor 4 alpha–positive) . This heterogeneity has rendered the identification of common, specific markers of DRCs quite challenging as different DRCs can express different markers depending on their origin and the nature of the injury .…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
“…Nevertheless, patients with chronic liver injury exhibit ductular reaction with increased levels of replicating BECs, which correlate with advanced stages of the disease. (1) In this regard, the contribution of the pluripotent BECs, derived from the small ducts of the intrahepatic biliary tree (i.e., canals of Hering), to hepatocyte mass restoration was suggested. Although the first studies reported a modest involvement of BECs in hepatocyte repopulation, (2) recent research work has demonstrated the capacity of BECs to transdifferentiate into hepatocytes upon impaired hepatocyte proliferation.…”
Section: See Article On Page 742mentioning
confidence: 99%
“…Under these circumstances, hepatocytes can enter into replicative senescence, leading to the exhaustion of their proliferative ability, and, therefore, are no longer able to regenerate the hepatic mass. Nevertheless, patients with chronic liver injury exhibit ductular reaction with increased levels of replicating BECs, which correlate with advanced stages of the disease . In this regard, the contribution of the pluripotent BECs, derived from the small ducts of the intrahepatic biliary tree (i.e., canals of Hering), to hepatocyte mass restoration was suggested.…”
mentioning
confidence: 99%
“…In addition to regulating ductal bicarbonate secretion, cholangiocytes are the target of cholangiopathies, which are liver diseases characterized by ductular reaction, enhanced biliary senescence (with increased secretion of senescence‐associated secretory phenotypes [SASPs]), and subsequent increased collagen deposition . Changes in ductular reaction are modulated by a number of neuroendocrine factors, such as agonists for serotonin receptor subtypes, melatonin, secretin, somatostatin, neurotransmitters, and sex hormones …”
mentioning
confidence: 99%